Enhanced photocatalytic degradation of nitrobenzene using MWCNT/β-ZnMoO4 composites under UV light emitting diodes (LEDs). (September 2020) - Natarajan, Kalithasan; Dave, Sruja; Bajaj, Hari C.; Tayade, Rajesh J.
Abstract: The β -ZnMoO4 /MWCNT nanocrystal composites were synthesized using hydrothermal method. The physicochemical properties such as structure, morphology and bandgap of synthesized photocatalysts were characterized using PXRD, UV-vis DRS, FTIR, FT-Raman, SEM and TEM analytical methods. PXRD pattern shows the peak shift in the case of synthesized ZnMoO4 /MWCNT which confirms the formation of nanocomposites. Moreover, the strong absorbance in UV region which was evidenced in UV-vis DRS spectra for all the case of synthesized ZnMoO4 and ZnMoO4 /MWCNT composites. From the SEM and TEM images, the MWCNT was found to have adhered over the ZnMoO4 nanocrystals. Compared to bare β -ZnMoO4, β -ZnMoO4 /MWCNT nanocrystal composites exhibited significant higher photocatalytic activity under ultraviolet light emitting diodes (UVLEDs) irradiation for the degradation of nitrobenzene (NB; 2.606 × 10 −4  M). This may be due to the effective charge transfer in the composite and optimized electron hole pair recombination. The photocatalytic activity of the synthesized photocatalysts was also studied under visible LEDs and it is observed that the photocatalytic degradation of NB was 97%, 77%, 65% and 52% under the irradiation of UV, blue, green, and red LEDs respectively. Graphical abstract: Image 1 Highlights: MWCNT/β-ZnMoO4 (MZM) nanocrystal composites synthesized via hydrothermal method. Nitrobenzene (NB) degradation using MZM nanocrystal composites under various LED irradiation were studied. The highest NB degradation under ultraviolet light emitting diodes (UVLEDs) irradiation was 97% in 120 min.